Estimating uniaxial compressive strength of tropically weathered sedimentary rock using indirect tests - Liang, Maybelle (Penerbit UTM Press, 2015)
Uniaxial compressive strength (UCS) of intact rock is particularly important in rock mechanic studies, especially for those involving civil and mining projects. However, the determination of UCS using direct test is generally expensive, time consuming and almost impossible in preparation of samples for highly weathered sedimentary rocks. In view of this, indirect tests are comparatively cheap, simpler, faster and more convenient to perform either in laboratory or at site. This paper aims to develop an estimation procedure in determining the UCS values of such weak weathered rocks. Among the indirect tests present herein are point load index, Schmidt Rebound hammer, Brazilian tensile test and slake durability test. Unfortunately, it was found that the accuracy of each single test varies with weathering states. Hence, a recommended procedure using combined indirect tests in determining UCS of weak sedimentary rocks is presented herein